Perkembangan pemikiran Ludwig Wittgenstein sebagai sarana refleksi terhadap Bhinneka Tunggal Ika = The Development of Ludwig Wittgenstein's Though as Reflection Mean to Bhinneka Tunggal Ika - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
This thesis described about .philosophical problems in Bhinneka Tunggal Ika in monism and pluralism perspectives. Wittgenstein is one of some analytical philosophers, who thought about linguistic problems in philosophy. His thinking divided into two periods. The first period was represented by Tractatus Loco-Philosoplucus, which assumed that we need uniformity in philosophical language. The second period was represented by The Philosophical Investigations, which assumed that our living has pluriformity in the ordinary language. Such ordinary language was expressed and represented by multiplicity of language-games, which have rule of games. The development of Wittgenstein's thought as reflection mean to Bhinneka Tunggal lka, where will be find out the main philosophical problems, namely the One and the Many, or unity and plurality, or uniformity and pluriformiW. The One and the Many were perennial problems in the history of Western philosophy, since Plato until contemporary .philosophies. An inquiry into reality arose two opinions, namely morusm and pluralism. Monism assumed that reality is singular, while pluralism assumed that reality is plural. Bhinneka Tunggal Ika as Indonesian symbol means that they are indeed different, but they are of the same kind. Bhinneka Tunggal Ika showed multi-ethnics, multi-linguistics, multi-religions in Indonesia, and all of them been synthesized in unity. The existence of Bhinneka Tunggal Ika categorically is different from Pancasila. The existence of Bhinneka Tunggal Ika is an "ought to" Indonesia to transcend multiplicity, while Pancasila is the First Princi- ple for Indonesia.